2007
DOI: 10.1152/jn.01148.2006
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Evoked Responses in Onset Chopper Neurons in Guinea Pig Cochlear Nucleus

Abstract: . Extracellular recordings were obtained from single cochlear nucleus neurons in guinea pigs anesthetized with Nembutal and Hypnorm. Neurons were classified by their spontaneous firing rates and responses to acoustic stimuli. In addition, electrical shocks were applied to the midline at the level of the IVth ventricle and spike responses were recorded. Spikes were evoked by shocks only in neurons that were classified as onset choppers (O c ). The shock-evoked spikes could be extinguished by acoustically evoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
(53 reference statements)
4
18
0
Order By: Relevance
“…It may be possible that the leftward shift is brought about by activation of MOC collaterals. Electron microscopical data suggest an excitatory action of MOC collaterals in the cochlear nucleus on both large and varicose dendrites (Winter et al, 1989;Benson and Potashner, 1990;Benson and Brown, 1990;Brown, 1993;Benson et al, 1996;Horvath et al, 2000) and previously we have obtained physiological evidence in support of a direct excitatory action of MOC collaterals on CN neurons (Mulders et al, 2002(Mulders et al, , 2003(Mulders et al, , 2007. This is in conflict with results of Seluakumaran et al (2008) who found that all effects of MOC stimulation on CNIC I/O functions in quiet were eliminated by gentamicin block of peripheral MOC action, suggesting that the MOC collaterals do not have an effect under these conditions.…”
Section: Effects Of Moc Activation On Masked Responsessupporting
confidence: 64%
“…It may be possible that the leftward shift is brought about by activation of MOC collaterals. Electron microscopical data suggest an excitatory action of MOC collaterals in the cochlear nucleus on both large and varicose dendrites (Winter et al, 1989;Benson and Potashner, 1990;Benson and Brown, 1990;Brown, 1993;Benson et al, 1996;Horvath et al, 2000) and previously we have obtained physiological evidence in support of a direct excitatory action of MOC collaterals on CN neurons (Mulders et al, 2002(Mulders et al, , 2003(Mulders et al, , 2007. This is in conflict with results of Seluakumaran et al (2008) who found that all effects of MOC stimulation on CNIC I/O functions in quiet were eliminated by gentamicin block of peripheral MOC action, suggesting that the MOC collaterals do not have an effect under these conditions.…”
Section: Effects Of Moc Activation On Masked Responsessupporting
confidence: 64%
“…Medial OC neurons are known to have collaterals projecting to the CN (Winter et al, 1989;Benson and Brown, 1990;Benson and Potashner, 1990;Brown, 1993;Benson et al, 1996;Horváth et al, 2000), and we have previously shown direct excitatory effects of these collaterals on CN neurons, in particular onset chopper neurons (Mulders et al, 2002(Mulders et al, , 2003(Mulders et al, , 2007). These neurons are thought to provide wide band inhibition to other CN neurons (Verhey et al, 2003;Arnott et al, 2004;Neuert et al, 2004) and could be responsible for the modulation of spontaneous activity remaining after cochlear strychnine.…”
Section: Discussionmentioning
confidence: 49%
“…Oc neurons still showed at least two distinct early peaks in their PSTHs (Fig. 2 D), very wide dynamic range and higher firing rates to noise than to pure tone stimuli (Winter and Palmer, 1995;Arnott et al, 2004;Mulders et al, 2007). Chopper-type and primary-like categories were easily distinguishable in these animals regardless of spontaneous firing rate (Fig.…”
Section: Methodsmentioning
confidence: 86%